The Effect of Using Talk Shows as Authentic Video Materials on Enhancing EFL Learners’ Speaking Fluency: A Case Study of Second-Year Bachelor Students at the University of Souk Ahras - Lydia GOUASMIA (My University, 2026)
Abstract This study aimed to examine the effect of using authentic English talk show videos on enhancing EFL learners’ speaking fluency. It also sought to explore learners’ perceptions regarding the use and effectiveness of these materials in speaking sessions. The study was guided by two hypotheses: (1) exposure to authentic talk show videos significantly improves learners’ speaking fluency, and (2) learners hold positive perceptions toward the use of talk show videos as pedagogical tools. A quasi-experimental design was adopted. The population consisted of second-year Bachelor students at the University of Souk Ahras, with a sample of 17 participants. Data were collected using a pre-test and post-test to measure speaking fluency, a classroom observation checklist administered across four sessions, and a focus group interview to gather qualitative insights. The results revealed a statistically significant improvement in learners’ speaking fluency, as the mean score increased from 10.00 in the pre-test to 11.41 in the post-test (p = 0.004). Improvement was particularly evident in continuity of speech, speech rate, and reduction of hesitation, while the use of fillers remained problematic. Observational data confirmed a gradual development of fluency across sessions. Additionally, qualitative findings indicated that learners held positive perceptions, reporting increased motivation, confidence, and engagement. These results support both research hypotheses. ------------------ الملخص تهدف هذه الدراسة إلى فحص أثر استخدام مقاطع فيديو أصلية من برامج الحوار الإنجليزية (Talk Shows) في تحسين الطلاقة الشفوية لدى متعلمي اللغة الإنجليزية كلغة أجنبية، بالإضافة إلى استكشاف تصوراتهم حول مدى فعالية هذه الوسائل التعليمية. اعتمدت الدراسة على فرضيتين: (1) أن التعرض لبرامج الحوار يحسن بشكل دال الطلاقة الشفوية، و(2) أن المتعلمين لديهم اتجاهات إيجابية نحو استخدامها. تم اعتماد منهج شبه تجريبي، حيث شملت الدراسة طلبة السنة الثانية ليسانس بجامعة سوق أهراس، وبلغ حجم العينة 17 طالباً. تم جمع البيانات باستخدام اختبار قبلي وبعدي لقياس الطلاقة، إضافة إلى بطاقة ملاحظة صفية خلال أربع حصص، ومقابلة جماعية للحصول على بيانات نوعية. أظهرت النتائج تحسناً ذا دلالة إحصائية في الطلاقة الشفوية، حيث ارتفع المتوسط من 10.00 في الاختبار القبلي إلى 11.41 في الاختبار البعدي (p = 0.004). وتم تسجيل أكبر تحسن في استمرارية الكلام وسرعة النطق وتقليل التردد، بينما ظل استخدام الحشو والتكرار يمثل صعوبة. كما أكدت الملاحظات الصفية وجود تطور تدريجي. وأظهرت النتائج النوعية أن الطلبة لديهم اتجاهات إيجابية، حيث ارتفعت مستويات الدافعية والثقة والمشاركة. وتدعم هذه النتائج فرضيتي الدراسة. --------------------- Résumé Cette étude vise à examiner l’effet de l’utilisation de vidéos authentiques de talk-shows anglais sur l’amélioration de la fluidité orale des apprenants en anglais langue étrangère (EFL). Elle cherche également à analyser les perceptions des apprenants quant à l’utilisation et à l’efficacité de ces supports. L’étude repose sur deux hypothèses : (1) l’exposition aux talk-shows améliore significativement la fluidité orale, et (2) les apprenants ont des perceptions positives envers ces supports pédagogiques. Une méthodologie quasi-expérimentale a été adoptée. La population ciblée est constituée des étudiants de deuxième année licence à l’Université de Souk Ahras, avec un échantillon de 17 participants. Les données ont été collectées à l’aide d’un pré-test et d’un post-test, d’une grille d’observation en classe sur quatre séances, ainsi que d’un entretien de groupe. Les résultats ont montré une amélioration statistiquement significative de la fluidité orale, avec une augmentation de la moyenne de 10.00 à 11.41 (p = 0.004). Les progrès les plus importants concernent la continuité du discours, le débit de parole et la réduction des hésitations, tandis que l’usage des fillers reste problématique. Les observations ont confirmé une progression progressive. De plus, les résultats qualitatifs révèlent des perceptions positives, notamment en termes de motivation, de confiance et d’engagement. Ces résultats confirment les deux hypothèses.
Keywords: Speaking Fluency; EFL learners; Authentic Materials; Talk Show Videos; Audiovisual Learning; الطلاقة الشفوية، متعلمو اللغة الإنجليزية كلغة أجنبية، المواد الأصيلة، مقاطع البرامج الحوارية، التعلم السمعي البصري.; Fluidité orale; apprenants EFL; supports authentiques; vidéos de talk-show; apprentissage audiovisuel